Endoscopic Doppler probe ultrasonography for detecting blood flow at post-endoscopic submucosal dissection ulcers of the stomach - Shiratori, Yasutoshi; Ikeya, Takashi; Oguri, Noriaki; Takasu, Ayaka; Okamoto, Takeshi; Fukuda, Katsuyuki (Endoscopy International Open, 2020)
Background and study aims The rate of early rebleeding after endoscopic submucosal dissection (ESD) for early gastric cancer ranges from 5 % to 38 %, despite application of preventive methods. Post-ESD rebleeding may be caused by “invisible” vessels that may not be detectable using ultrasonographic techniques. Recently, Doppler probe ultrasonography (DOP) has been used in endoscopy. Because little is known about the usefulness of DOP for decreasing the post-ESD rebleeding rate, we performed a preliminary case series study.Patients and methods Twelve patients underwent DOP for post-ESD ulcer evaluation after visible vessel coagulation. In this study, the novel DOP system used in the vascular surgery department was used. DOP-positive invisible vessels were shown as a pulse wave on the monitor.Results No (0 %) cases of post-ESD rebleeding occurred. Twenty invisible vessels were detected, and 13 were subjected to additional coagulation up to a depth of 3 mm. Mean DOP procedure time was 11.6 minutes (range: 8–18 minutes). In these latter cases, disappearance of the Doppler pulse wave was confirmed. No early rebleeding or other adverse events were experienced.Conclusion DOP is a safe and feasible method for detecting invisible vessels in post-ESD ulcers. Further investigation of the clinical relevance is warranted.